Dampak Cyberbullying Pada Remaja di Media Sosial - Mohamad Siroj; Amalia Zulfa (PT. Intelek Cendikiawan Nusantara, 2024)
Nowadays, the development of social media is very rapid, with very easy access and unlimited scope of friendship so that all groups, regardless of social status, from old, young, even children, are very enthusiastic about using social media, especially teenagers. Social networks are also used as a place to express emotional outbursts, and it is not uncommon to express anger in the form of abuse or insults which is often called cyberbullying. The purpose of this writing is to determine the impact of cyberbullying on teenagers on social media. The method used is a literature study using written sources such as books, journals, sources from archives, articles, the internet, etc. related to information about the impact of cyberbullying on teenagers. The results of various studies show that cyberbullying in teenagers on social media has a huge impact that affects all aspects of life ranging from psychological, physical and social aspects.